BK Channel β1 Subunit Contributes to Behavioral Adaptations Elicited by Chronic Intermittent Ethanol Exposure. (18th November 2015) - Kreifeldt, Max; Cates‐Gatto, Chelsea; Roberts, Amanda J.; Contet, Candice
Abstract : Background: Large conductance, calcium‐ and voltage‐activated potassium (BK) channels regulate neuronal excitability and neurotransmission. They can be directly activated by ethanol (EtOH) and they may be implicated in EtOH dependence. In this study, we sought to determine the influence of the auxiliary β 1 and β 4 subunits on EtOH metabolism, acute sensitivity to EtOH intoxication, acute functional tolerance, chronic tolerance, and handling‐induced convulsions during withdrawal. Methods: Motor coordination, righting reflex, and body temperature were evaluated in BK β 1 and β 4 knockout, heterozygous, and wild‐type mice following acute EtOH administration. Chronic tolerance and physical dependence were induced by chronic intermittent inhalation of EtOH vapor. Results: Constitutive deficiency in BK β 1 or β 4 subunits did not alter the clearance rate of EtOH, acute sensitivity to EtOH‐induced ataxia, sedation, and hypothermia, nor acute functional tolerance to ataxia. BK β 1 deletion reduced chronic tolerance to sedation and abolished chronic tolerance to hypothermia, while BK β 4 deletion did not affect these adaptations to chronic EtOH exposure. Finally, the absence of BK β 1 accelerated the appearance, while the absence of BK β 4 delayed the resolution, of the hyperexcitable state associated with EtOH withdrawal. Conclusions: Altogether, the present findings reveal the critical role of BK β 1 in behavioral adaptations to prolonged, repeated EtOH intoxication. Abstract : Figure 4 . Ethanol‐induced hypothermia and chronic tolerance in BK β1‐ and β4‐deficient mice. The hypothermic effect of ethanol (4 g/kg, i.p.) was measured in BK β1 ((A ) WT, n = 7; Het, n = 8; KO, n = 5) and BK β4 ((B ) WT, n = 9; Het, n = 8; KO, n = 8) mice. CIE exposure produced tolerance to hypothermia in both strains, as reflected by a smaller drop in body temperature post‐CIE (black stars: two, p < 0.01; three stars, p < 0.001). There was a significant effect of genotype in BK β1 mice post‐CIE 60 and 120 min postinjection, as well as in BK β4 mice prior to the injection (white stars, p < 0.05).